Perbandingan Implementasi Smart City di Indonesia: Studi Kasus: Perbandingan Smart People di Kota Surabaya dan Kota Malang - Pramesti, Dyah Ratna; Kasiwi, Aulia Nur; Purnomo, Eko Priyo (HK-Publishing, 2020)
This study focuses on the problem of smart people as an indicator of the success of smart cities in Surabaya and Malang. Smart people are one of the supporting dimensions of the creation of a smart city or what is called a Smart City (Zubizarreta, Seravalli, And, Arrizabalaga, 2016). So that the factors that make a city smart, one of which is measured by the quality of its human resources; which includes the human development index which is measured by how the level of unemployment, poverty level, health problems, and also seen from the aspect of public knowledge in receiving information, disseminating information, related to the development of creativity carried out and also the inclusiveness of empowering activities carried out by several people. (Iyer, 2018). In addition, the activities that are encountered in the city of Surabaya in community activities, already have quite innovative and creative networks. Meanwhile, Malang City is still heading for the stage of good quality. There needs to be motivation and encouragement so that Malang City is able to follow in the footsteps of the development of smart people in the city of Surabaya.Penelitian ini berfokus pada masalah smart people sebagai indicator keberhasilan smart city di Kota Surabaya dan Kota Malang. Smart people merupakan salah satu dimensi pendukung dari terwujudnya kota pintar atau yang disebut dengan Smart City (Zubizarreta, Seravalli, And, Arrizabalaga, 2016). Sehingga faktor-faktor yang menjadikan sebuah kota dapat dikatakan pintar salah satunya diukur dari kualitas sumber daya manusianya; yang meliputi dari indeks pembangunan manusianya yang diukur dari bagaimana tingkat pengamgguran, tingkat kemiskinan, masalah kesehatan, dan juga dilihat dari aspek pengetahuan masyarakat di dalam menerima informasi, menyebarkan informasi, terkait dengan penumbuhan kratifitas yang dilakukan dan juga inklusivitas pemberdayaan kegiatan yang dilakukan oleh beberapa orang (Iyer, 2018).Â Selain itu, aktifitas yang ditemui di Kota Surabaya dalam kegiatan komunitasnya, sudah memiliki jaringan yang cukup inovatif dan juga kreatif. Sedangkan untuk di Kota Malang masih menuju tahapan kualitas yang baik. Perlu adanya motivasi dan dorongan supaya Kota Malang mampu mengikuti jejak perkembangan smart people yang ada di Kota Surabaya.